A Comparative Study of Three Different Chemical Vapor Deposition Techniques of Carbon Nanotube Growth on Diamond Films. (31st March 2013) - Quinton, Betty T.; Barnes, Paul N.; Varanasi, Chakrapani V.; Burke, Jack; Tsao, Bang-Hung; Yost, Kevin J.; Mukhopadhyay, Sharmila M.
Abstract : This paper compares between the methods of growing carbon nanotubes (CNTs) on diamond substrates and evaluates the quality of the CNTs and the interfacial strength. One potential application for these materials is a heat sink/spreader for high-power electronic devices. The CNTs and diamond substrates have a significantly higher specific thermal conductivity than traditional heat sink/spreader materials making them good replacement candidates. Only limited research has been performed on these CNT/diamond structures and their suitability of different growth methods. This study investigates three potential chemical vapor deposition (CVD) techniques for growing CNTs on diamond: thermal CVD (T-CVD), microwave plasma-enhanced CVD (MPE-CVD), and floating catalyst thermal CVD (FCT-CVD). Scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (TEM) were used to analyze the morphology and topology of the CNTs. Raman spectroscopy was used to assess the quality of the CNTs by determining the I D /I G peak intensity ratios. Additionally, the CNT/diamond samples were sonicated for qualitative comparisons of the durability of the CNT forests. T-CVD provided the largest diameter tubes, with catalysts residing mainly at the CNT/diamond interface. The MPE-CVD process yielded non uniform defective CNTs, and FCT-CVD resulted in the smallest diameter CNTs with catalyst particles imbedded throughout the length of the nanotubes.